Menjadi Guru Abadi: Membuat Koneksi yang Benar, Menegakkan Standar Etika dan Serapan Materi Pelajaran Tinggi - Cahyo, Hariris Nur (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
Changes in society do not occur without structural and cultural changes that are influenced by internal and external factors of the community itself. Indonesians generally believe that school is a strong institution in transforming culture into future generations, despite the fact that cultural transformation occurs more often than interaction or social contact between students and the community outside of school. Teaching in class is an eternal aspect of teaching that requires time and patience, the teacher cares about the social foundation of education with the desire for participatory democracy, shifts the emphasis from following leaders to being leaders of social ethics, understanding each other, listening, and learning from each other. teachers are strong precisely because they teach us who we are, and show us who we can be. Anxiety that develops around intergenerational touch settings has emerged and increased in recent years. Teachers are sometimes reluctant to connect with students in fashion and the prospect of teaching and learning from behind the classroom in any way. Some teachers are still not able to build a true relationship with students, in fact, have not succeeded in achieving the target, producing a clear and convincing and fatal narrative is the teacher's deep self-confidence because his teacher failed to unravel his hopes that students obey the directions in the hope ability As a result, ethical standards cannot be enforced and absorption of subject matter becomes low. This paper aims to describe being an eternal teacher: making the right connections, upholding ethical standards and uptake of high learning material. The results of the discussion can be concluded: 1) Teachers need a more comprehensive approach. Many schools are starting to try various programs, hoping to better serve these students. The basis of many programs is the call for stable, positive learning and student relations. 2) Teacher support outside the class arena in depth looks at the meaning of teaching outside the classroom to activate a particular curriculum and context in the school as a whole, with a special focus on communication, collaboration and collaboration in the wider school community. 3) Good teachers already know not to use sarcasm, not to mention children, in front of their friends. We don't need to visit effective teacher classrooms to learn this. But we can always reap good ideas from successful educators. 4) working with students is never as simple as yes or no, bad or good, right or wrong. Teaching is more like an open essay exam. This will not help many of the most unprepared test takers; On the other hand, even though we might disagree with everything in the best essay, we can still learn from it. At the very least, we might see some new ideas that we can build